Tuning the mechanical flexibility of organic molecular crystals by polymorphism for flexible optical waveguides. Issue 34 (13th August 2021) - Feiler, Torvid; Bhattacharya, Biswajit; Michalchuk, Adam A. L.; Rhim, Seon-Young; Schröder, Vincent; List-Kratochvil, Emil; Emmerling, Franziska
Abstract : The ability to selectively tune the optical and the mechanical properties of organic molecular crystals offers a promising approach towards developing flexible optical devices. Abstract : The ability to selectively tune the optical and the mechanical properties of organic molecular crystals offers a promising approach towards developing flexible optical devices. These functional properties are sensitive to crystallographic packing features and are hence expected to vary with polymorphic modification. Using as a model system the photoluminescent material 4-bromo-6-[(6-chloropyridin-2-ylimino)methyl]phenol (CPMBP), we herein demonstrate the simultaneous tuning of mechanical flexibility and photoluminescence properties via polymorphism. Two new polymorphic forms of CPMBP were obtained from a solution and fully characterised using a combination of experiments and density functional theory simulations. These polymorphic forms exhibit remarkably distinct mechanical properties and an order of magnitude difference in photoluminescence quantum yield. The mechanically plastic form has a higher quantum yield than the brittle polymorphic form. However, their photoluminescence emission profile is largely unaffected by the observed polymorphism, thereby demonstrating that the optical properties and bulk mechanical properties can in principle be tuned independently. By distinguishing between active (involving absorption and emission) and passive (involving no absorption) light propagation, the waveguiding properties of the plastic form of CPMBP (form II) were explored using the straight and bent crystals to highlight the potential applications of CPMBP in designing flexible optical devices. Our results demonstrated that polymorph engineering would be a promising avenue to achieve concurrent modulation of the optical and mechanical properties of photoluminescent molecular crystals for next-generation flexible optical device applications.